Evaluation of Occupational Accident Risk in the Implementation of Occupational Safety and Health (K3) at the Transpark Cibubur Project - Subagijo, Djoko; Erman, Satrio Anggito (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
The importance of implementing the K3 program is always a concern so that the program becomes better and work accidents can be minimized. Like a work accident in a construction project. The process of building construction projects in general is an activity that contains many elements of danger. The situation in the project location reflects a tough character and the activities look very complex and difficult to carry out so that excellent stamina is needed from the workers who carry it out. However, it cannot be denied that this construction work is a contributor to a fairly high number of accidents. The number of cases of work accidents and occupational diseases is very detrimental to many parties, especially the workers concerned (Ervianto, 2005.) The application of K3 programs in development projects is also important because the risk of accidents is high. In addition, it must also be supported by the awareness of workers to maintain personal safety while working has increased. It can be seen from the number of accidents. And the case of employment problems. Based on data, companies that have successfully implemented the OHS Management program have increased to 1,221 companies. This number is up about 69.1 percent from 2016. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US ZH-CN HI <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The importance of implementing the K3 program is always a concern so that the program becomes better and work accidents can be minimized. Like a work accident in a construction project. The process of building construction projects in general is an activity that contains many elements of danger. The situation in the project location reflects a tough character and the activities look very complex and difficult to carry out so that excellent stamina is needed from the workers who carry it out. However, it cannot be denied that this construction work is a contributor to a fairly high number of accidents. The number of cases of work accidents and occupational diseases is very detrimental to many parties, especially the workers concerned (Ervianto, 2005.) The application of K3 programs in development projects is also important because the risk of accidents is high. In addition, it must also be supported by the awareness of workers to maintain personal safety while working has increased. It can be seen from the number of accidents. And the case of employment problems. Based on data, companies that have successfully implemented the OHS Management program have increased to 1,221 companies. This number is up about 69.1 percent from 2016.